Gastric Cancer - An Update 2019
DOI: 10.5772/intechopen.75591
|View full text |Cite
|
Sign up to set email alerts
|

Reconstructive Procedures after Total Gastrectomy for Gastric Cancer

Abstract: Till this day, there are more than 60 described surgical procedures of the intestinal reconstructions after a total gastrectomy. In 1897, Schlatter reconstructed the digestive tract by creating a termino-lateral esophagojejunostomies that was the first successful total gastrectomy. Many of the total gastrectomy pioneers did the reconstruction by esophagoduodenostomy or by forming a loop esophagojejunostomy. The main reconstruction modalities after a total gastrectomy are a restitution of the intestinal continu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 47 publications
0
4
0
Order By: Relevance
“…There are conflicting reports of who invented the DTR technique, but a study reports that it was first mentioned by Japanese surgeons Kajitani and Sato [ 9 ]. DTR is classified as a duodenal preserving reconstructive method because it maintains the passage of food into the duodenum for digestion [ 10 ]. In this section the surgical procedure of DTR after PG is briefly explained.…”
Section: Surgical Procedure/surgical Backgroundmentioning
confidence: 99%
See 1 more Smart Citation
“…There are conflicting reports of who invented the DTR technique, but a study reports that it was first mentioned by Japanese surgeons Kajitani and Sato [ 9 ]. DTR is classified as a duodenal preserving reconstructive method because it maintains the passage of food into the duodenum for digestion [ 10 ]. In this section the surgical procedure of DTR after PG is briefly explained.…”
Section: Surgical Procedure/surgical Backgroundmentioning
confidence: 99%
“…After gastrectomy, surgical reconstruction aims at maintaining intestinal continuity, decreasing post-operative complications, and preserving good nutritional status. Gastric reconstructive procedures can be designed to either preserve the duodenal passage or without preserving the duodenal passage for food [ 4 , 10 ]. Many researchers have argued over the benefits of maintain the duodenal passage of food.…”
Section: Effect On Postoperative Complicationsmentioning
confidence: 99%
“…They may even experience symptoms such Nutrients 2022, 14, 2634 2 of 12 as nausea, vomiting, bloating, abdominal pain, and diarrhea or suffer dysphagia [5]. Severe symptoms can cause further psychological distress [7] and negatively impact the patient's food intake [8,9]. Emotional distress, symptom disturbance, and cancer-related inflammation can increase protein energy-wasting, which leads to reduced body weight [10].…”
Section: Introductionmentioning
confidence: 99%
“…Knowledge regarding factors influencing patients' nutritional status can inform the development of appropriate measures to improve patients' nutrition quality. Previous studies have shown that gastrointestinal symptoms [8], depression [7], and difficulties with diet preparation [19] might affect the nutrient intake of patients. However, most of these studies were conducted in western countries on patients with other cancers.…”
Section: Introductionmentioning
confidence: 99%